Comparing the Rates of Dopamine Hemodynamic Effect Onset after Infusion through Peripheral Veins in Three Regions - Kim, Deokkyu (Korean J Crit Care Med, 2017)
BACKGROUND: Dopamine is an inotropic agent that is often selected for continuous infusion. For hemodynamic stability, the rate of infusion is controlled in the range of 5-15 μg/kg/min. This study aimed to compare the time intervals from the administration of dopamine to the onset of its hemodynamic effects when dopamine was administered through three different peripheral veins (the cephalic vein [CV], the great saphenous vein [GSV], and the external jugular vein [EJV]). METHODS: Patients in group 1, group 2, and group 3 received dopamine infusions in the CV, GSV, and EJV, respectively. A noninvasive continuous cardiac output monitor (NICCOMO™, Medis, Ilmenau, Germany) was used to assess cardiac output (CO) and systemic vascular resistance (SVR). Six minutes after intubation, baseline heart rate (HR), systolic blood pressure (BP), diastolic BP, mean arterial pressure (MAP), CO, and SVR values were recorded and dopamine infusion was initiated at a dose of 10 μg/kg/min. Hemodynamic changes at 0, 4, 8, 12, and 15 minutes postinfusion were recorded. RESULTS: No statistically significant differences were observed among the three groups with respect to the rate of hemodynamic change. In all groups, systolic BP, diastolic BP, MAP, and SVR tended to increase after decreasing for the first 4 minutes; in contrast, HR and CO decreased until 8 minutes, after which they tended to reach a plateau. CONCLUSIONS: For patients under general anesthesia receiving dopamine at 10 μg/kg/min, there were no clinical differences in the effect of dopamine administered through three different peripheral veins.